PENGARUH DANA PIHAK KETIGA, LDR, DAN BOPO TERHADAP JUMLAH PENYALURAN KREDIT PERBANKAN - Retno Widyawati, - (2018)
The purpose of this study is to examine Influence of Third-Party Funds, LDR and BOPO to Total of Loans. The population used in this study is a commercial bank listed on the Indonesia Stock Exchange (BEI) and Indonesia Bank (BI) in the period 2013-2016. By using purposive sampling method, it is obtained as many as 41 banks as the study sample. The method of analysis used in this study is multiple linier regression. In this research also include the classical assumption that normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Results of this study indicate that the third-party funds and loan to deposit ratio (LDR) significant positive effect to total of loans. While and operating expenses to operating income (BOPO) are not significant effect to total of loans.